Exercise for mild balance dysfunction: Research into practice - Williams, S.; Meyer, C.; Batchelor, F.; Hill, Keith (2015)
The objective of this study was to determine whether improved balance outcomes achieved in a randomized controlled trial (RCT) using balance screening to identify mild balance dysfunction and home exercises could be translated into community settings. Community-dwelling people aged over 65 who expressed concerns about their balance, had less than two falls in the preceding 12 months, and who had mild balance impairment on screening were given an individualized home-based balance and strengthening exercise program with intermittent home-visit support by a physiotherapist. Of 71 participants assessed (mean age 77.3 years, 76% female), 58 (82%) completed the six-month intervention. Twenty six percent of participants regained balance performance within normal limits - similar to those achieved in the previous RCT. Successful results from a previous RCT were able to be translated into community settings, with a similar magnitude of effect on balance and mobility.